Recombinant chicken interleukin-7 as a potent adjuvant increases the immunogenicity and protection of inactivated infectious bursal disease vaccine - Cui, Dan (Vet Res, 2018)
Our previous work showed that a plasmid-based chicken interleukin-7 (chIL-7) gene expression vector possessed potent adjuvant activity for a VP2 DNA vaccine against chicken infectious bursal disease virus (IBDV). Whether recombinant chIL-7 prepared in procaryotic expression system has the adjuvant activity for inactivated IBDV vaccine remains unknown. Here, we prepared recombinant chIL-7 using an E. coli expression system and analyzed its adjuvant activity for the inactivated IBDV vaccine. The results show that the recombinant chIL-7 was successfully prepared in E. coli using the pET20b vector, which possessed biological activity to stimulate mouse B lymphocyte proliferation. Co-administration of the chIL-7 with inactivated IBDV vaccine significantly increased specific serum antibody titers against IBDV, enhanced lymphocyte proliferation and IFN-γ and IL-4 productions, and increased protection against virulent IBDV infection.